2019
DOI: 10.1073/pnas.1909550116
|View full text |Cite
|
Sign up to set email alerts
|

Transient enhancement of p53 activity protects from radiation-induced gastrointestinal toxicity

Abstract: Gastrointestinal (GI) syndrome is a serious side effect and dose-limiting toxicity observed in patients undergoing lower-abdominal radiotherapy. Previous mouse studies show that p53 gene dosage determines susceptibility to GI syndrome development. However, the translational relevance of p53 activity has not been addressed. Here, we used a knock-in mouse in which the p53–Mdm2 negative feedback loop is genetically disrupted. These mice retain biallelic p53 and thus, normal basal p53 levels and activity. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…In summary, our results provide novel insight into a long-standing question in radiation biology: how does the tumor suppressor p53 suppress the development of the radiation-induced GI syndrome? 8,[20][21][22] Our results indicate that transient activation of p53 after irradiation is necessary to promote the emergence of revSCs. We demonstrate that Clu+ revSCs contribute to a significant fraction of regenerating epithelial crypts during the radiation-induced GI syndrome and the revSCs have also been previously shown to increase animal survival following gut damage 5 .…”
Section: Main Textmentioning
confidence: 62%
“…In summary, our results provide novel insight into a long-standing question in radiation biology: how does the tumor suppressor p53 suppress the development of the radiation-induced GI syndrome? 8,[20][21][22] Our results indicate that transient activation of p53 after irradiation is necessary to promote the emergence of revSCs. We demonstrate that Clu+ revSCs contribute to a significant fraction of regenerating epithelial crypts during the radiation-induced GI syndrome and the revSCs have also been previously shown to increase animal survival following gut damage 5 .…”
Section: Main Textmentioning
confidence: 62%
“…We previously reported 5-chloro-8-quinolinol as a modulator of p53 transactivation that effectively inhibits the GI syndrome through the induction of p21. Others demonstrated similar results by using RG7112, a chemical compound that activates p53-p21 pathway through the inhibition of p53-Mdm2 interaction [26]. Considering the fact that isorhamnetin moderately inhibited p53-p21 pathway in irradiated MOLT-4 cells, it would exert the suppressive effect against GI death independent of p53.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, previous studies found a significant decrease in p53 expression at 8 Gy radiation dose, supporting the present investigation [ 41 ]. Pretreatment with L-NAT to irradiated Neuro2a cells led to enhanced p53 expression as compared to irradiated cells (1.29 fold; p <0.05; Figures 11(c) , 11(f) and 11(g) ), further justified a prominent role of p53 in DNA repair and cell cycle arrest, which provides crucial time for the activation of various DNA-repair systems [ 46 , 47 ]. Pretreatment with L-NAT to irradiated Neuro2a cells showed a significant reduction in DNA damage compared to irradiated cells in the comet assay and a decrease in γ -H2aX protein expression that may correlate with an increase in p53 activity ( Figure 5(b) and 11(b) – 11(c) ).…”
Section: Discussionmentioning
confidence: 97%